(untitled) (Microbes and Health, 2014)
Brucellosis is a zoonotic bacterial disease of humans and animals caused by Gram negative bacteria of the genus Brucella. The study was conducted to determine the sero-prevalence of brucellosis and its associated risk factors in cattle and buffalo in greater Mymensingh district, Bangladesh. Blood samples were collected from cattle (n=150) and buffalo (n=60). Sera were tested for Brucella specific antibody by the rose Bengal plate test (RBPT). Overall prevalence of brucellosis was 15.33% in cattle and 13.33% in buffalo. Higher prevalence was recorded in cattle and buffalo of over 4 years age (18% and 15.68%, respectively). Female animals showed higher brucellosis prevalence (cattle 19.54%, buffalo 13.46%) than male ( cattle 8.21%, buffalo 12.5%). Pregnant cows showed higher prevalence of brucellosis (13.33%) as compare to non pregnant cows (10%). The prevalence of brucellosis was 10% in aborted cows, 4% in the case of retained placenta and 2.85% in repeat breeder cows. The study suggests that brucellosis is prevalent in the cattle and buffalo and its prevalence is affected by the animals age, sex, pregnancy status and reproductive disorders. Microbes and Health, June 2013, 2(1): 12-14 DOI: http://dx.doi.org/10.3329/mh.v2i1.17256